2022
DOI: 10.1093/tas/txac151
|View full text |Cite
|
Sign up to set email alerts
|

Improving beef calf health: frequency of disease syndromes, uptake of management practices following calving, and potential for antimicrobial use reduction in western Canadian herds

Abstract: Bovine respiratory disease (BRD), calf diarrhea (CD), and navel infections are the most commonly reported diseases of western Canadian beef calves. The objectives of this study were to estimate the frequency of treatment for these diseases for specific age cohorts and identify potential opportunities for reducing antimicrobial use. Producers representing 89 western Canadian cow-calf herds completed a survey describing calfhood diseases and management. The most common reason for calf treatment before weaning wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…The reason for this association could be that, typically, calves are separated from their mother and comingled with other calves while producers process the cows, temporarily increasing animal stress and density, thereby potentially increasing the risk of pathogen transmission. This finding is consistent with previous reports from other studies [ 13 , 15 , 16 ] that identified the increasing number of times cow–calf pairs were gathered before turning out to summer pasture and estrus synchronization as risk factors for respiratory disease in calves before weaning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reason for this association could be that, typically, calves are separated from their mother and comingled with other calves while producers process the cows, temporarily increasing animal stress and density, thereby potentially increasing the risk of pathogen transmission. This finding is consistent with previous reports from other studies [ 13 , 15 , 16 ] that identified the increasing number of times cow–calf pairs were gathered before turning out to summer pasture and estrus synchronization as risk factors for respiratory disease in calves before weaning.…”
Section: Discussionsupporting
confidence: 93%
“…For evaluating risk factors for AMU for cow lameness, herds were classified depending on whether they purchased more cattle than the median value for all herds throughout the year. Potential risk factors were selected based on previous publications [ 6 , 13 ] and expert opinion.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the use of larger pastures for calving was associated with fewer calves treated for navel or joint infection, and calves in herds from the west had a lower risk of treatment and death from diarrhea than herds from the east where barn use and shelters are more common. The risks associated with not using large pastures was consistent with a recent paper examining data from the WCCCSN ( 25 ) that showed using high-density calving areas, such as pens or barns vs. pasture, or failure to use the Sandhills or similar calving management systems were associated with higher risks of calf diarrhea in specific age groups and navel ill. Previous reports also describe the impact of more crowded conditions on opportunities for direct transmission from infected animals or indirect transmission through environmental contamination and the associated value of the Sandhills calving management system ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous postmortem examination studies with information on the age of calf death between 24 h and weaning reported 68% of calf deaths in the first 30 days after calving ( 23 , 24 ). Another more recent study based on questionnaire data also found that most calf death loss occurred within the first month ( 25 ). While the WCCCSN did not collect data on when calf deaths occurred from birth to weaning, the current study asked producers to report losses between 24 h and 30 days after birth, which was at or before the time most spring calving herds would have been moving their herds to summer pastures.…”
Section: Discussionmentioning
confidence: 86%
“…Annual Campylobacter and Leptospira revaccination are not considered core vaccines by the American Association of Bovine Practitioners, but are recommended for herds considered to be at high risk for either of these infections due to biosecurity challenges, comingling on community pastures or geographic location ( 19 , 20 ). Waldner et al reported similar vaccination trends for BVDV in cows, but higher levels of bacterial respiratory vaccines in cows ( 39 ).…”
Section: Discussionmentioning
confidence: 87%